Ventriculoperitoneal shunt for giant porencephaly: a case report and literature review - Lu, Dongsheng; Tan, Jialiang; Xu, Haitong (Frontiers in Surgery, 2024)
Porencephaly(POR) is an exceedingly rare neurological disorder characterized by the presence of solitary or multiple regressive cerebrospinal fluid(CSF) cavities within the brain parenchyma. Currently, there is a limited understanding of the pathogenesis and treatment options for this condition, and clinical presentations can vary significantly. However, imaging plays a crucial role in diagnosis and determining the optimal treatment strategy, necessitating individualized comprehensive treatment upon detection. We reported a 25-year-old male case with persistent head pain that did not resolve with rest. Magnetic resonance imaging (MRI) confirmed the giant POR, and we finally performed a ventriculoperitoneal shunt, and the symptoms of intracranial hypertension were relieved after surgery.